Artesano de palabras - Zuluaga Mesa, David Esteban (Universidad Católica Luis Amigó, 2021)
Craftsman of Words is a literary bet classified in the book album mode, which uses image and text as a vehicle to introduce the reader into a mix of everyday situations in which language and creativity are the main protagonists. The book seeks that the reader enhances processes of literal, abductive, symbolic and visual reading giving rise to the saying of others with which alternative plots and strategies can be sketched to enhance the development, not only of literacy skills, but also socio-affective and creative. The layout of the book allows, once its reading is finished, the development of new plots according to the interests and motivations of the reader or reading promoter that accompanies the process.